Role of adipokines, oxidative stress, and endotoxins in the pathogenesis of non-alcoholic fatty liver disease in patients with type 2 diabetes mellitus - M., Pallavi; M., Suchitra M.; Sachan, Alok; Y., Lakshmi A.; P. V. L. N., Srinivasa Rao (International Journal of Research in Medical Sciences, 2019)
Background: Type 2 diabetes mellitus (T2DM) is associated with chronic inflammation and oxidative stress, implicated in the pathophysiology of non-alcoholic fatty liver disease (NAFLD). Present study aimed to assess the role of adipokines, oxidative stress, and endotoxins in the pathogenesis of NAFLD in T2DM. Methods: Present cross-sectional observational study included healthy controls (n=50; group 1); T2DM patients without NAFLD (n=50; group 2), T2DM patients with NAFLD (n=50; group 3). Study subjects were age and gender matched. Results: Tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), high sensitive C-reactive protein (hs-CRP), endotoxin, malondialdehyde (MDA) were significantly elevated and adiponectin, ferric reducing ability of plasma (FRAP), and glutathione (GSH) were significantly lower (p<0.001) in T2DM patients with NAFLD when compared to T2DM patients without NAFLD and controls. Endotoxin showed significant positive correlation with TNF-α (r=0.304; p<0.001), hs-CRP (r=0.193; p=0.018), and MDA (r=0.420; p<0.001), and significant negative correlation with adiponectin (r=-0.406; p<0.001). TNF-α and IL-6 showed significant positive correlation with MDA (r=0.526; p<0.001, r=0.229; p=0.005) and significant negative correlation with adiponectin (r=-0.396; p<0.001, r=-0.318; p<0.001), FRAP (r=-0.418; p<00.001, r=-0.170; p=0.038), and GSH (r=-0.353; p<0.001, r=-0.301; p<0.001). Conclusions: Authors observed elevated endotoxin, oxidative stress, inflammation and lower adiponectin levels in T2DM subjects compared to controls. These changes were more pronounced in T2DM with NAFLD when compared to T2DM without NAFLD. Lower adiponectin levels were found to be a better predictor of NALFD in T2DM and is associated with oxidative stress and systemic inflammation.